High Frequency Response Current Self-Demodulation Method for Sensorless Control of Interior Permanent Magnet Synchronous Motor - Wenzhen Li (IEEE, 2021)
In the sensorless control, high frequency (HF) rotating sinusoidal voltage injection method requires the position error compensation algorithms to eliminate the side effect of system delay. However, the implementation complexity of the system is increased and the optimization of dynamic performance is hard to realize. This paper presents a system delay-free rotor demodulation method without constructing assistive demodulation signal and using position error compensation algorithm. The improvement of position estimation accuracy and the simplification of rotor position demodulation are achieved in the proposed method. Firstly, the side effect of the system delay on HF induced current and rotor position estimation is analyzed in detail. Secondly, the idea of eliminating system delay angle in HF current is proposed based on vector operations. The positive- and negative-sequence components of HF current are used to demodulate rotor position information by a vector algorithm. Simultaneously, the system delay angle is offset in the demodulation process. Thirdly, the rotor position angle is precisely solved by a normalized PLL. Furthermore, the proposed method can also be applied for both HF rotating voltage injection and HF orthogonal square-wave voltage injection. The effectiveness and advantages of the proposed method are validated experimentally.